2022
DOI: 10.1155/2022/3486313
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Effect and Safety Analysis of 2.5 μg/kg DEX Nasal Drop in Child Undergoing Ultrasound Examination

Abstract: In order to meta-analyze the clinical effect and safety of dexmedetomidine (DEX) intranasal sedation in child ultrasound examination, literature retrieval is carried out in Wanfang Medicine, PubMed database, domestic medical research journals. The relevant medical information literature on clinical effects and safety are analyzed by using Rev Man 5.2 software. The retrieved literature is screened according to the research object, method, disease type and other criteria. The results of meta-analysis show that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…60-year-old women are a high-risk group of osteoporosis. With the aging of society becoming more serious, the incidence of osteoporosis is increasing year by year [ 1 ]. Patients with osteoporosis are often accompanied by symptoms of reduced bone mineral density and increased risk of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…60-year-old women are a high-risk group of osteoporosis. With the aging of society becoming more serious, the incidence of osteoporosis is increasing year by year [ 1 ]. Patients with osteoporosis are often accompanied by symptoms of reduced bone mineral density and increased risk of fracture.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%